A Case of Gallbladder Metastasis From Renal Cell Carcinoma Detected via PSMA PET-CT - Khairil Anwar, Hannan; Chan, Kin Wong (Journal Of Cardiovascular, Neurovascular & Stroke, 2025)
Metastatic renal cell carcinoma is seen in about 30-40% of patients, with 20-50% developing metastasis after radical nephrectomy. Common organs of metastasis to the gallbladder from renal cell include the kidney, lung, bones and liver. We report a patient with underlying dual primary cancer, (metastatic castrate resistant prostate carcinoma as well as metastatic renal clear cell carcinoma) who was incidentally found to have hypermetabolic uptake in the gallbladder during interim PSMA PET-CT. A pre-operative CT pancreas protocol was performed, which showed a soft tissue lesion in the gallbladder. Subsequently, the patient underwent a laparoscopic cholecystectomy. The histopathology results of the gallbladder came back as metastatic clear cell renal cell carcinoma in a background of chronic cholecystitis. Currently, PSMA PET-CT is used as used as a diagnostic imaging tool to detect, stage and monitor prostate cancer, such as in our patient who had dual prostate and renal cell carcinoma. To our knowledge, this is the first case of metastatic gallbladder disease from renal cell carcinoma which was detected via PSMA PET-CT. Thus, we believe there is value in utilising the PSMA PET-CT for surveillance in patients with positive history of renal cell carcinoma.